The cytokine temporal profile in rat cortex after controlled cortical impact - Dalgard, Clifton L.; Cole, Jeffrey T.; Kean, William; Lucky, Jessica; Sukumar, Gauthaman; McMullen, David; Pollard, Harvey B.; Watson, William D. (Frontiers in Molecular Neuroscience, 2012)
Cerebral inflammatory responses may initiate secondary cascades following traumatic brain injury. Changes in the expression of both cytokines and chemokines may activate, regulate, and recruit innate and adaptive immune cells associated with secondary degeneration, as well as alter a host of other cellular processes. In this study, we quantified the temporal expression of a large set of inflammatory mediators in rat cortical tissue after brain injury. Following a controlled cortical impact on young adult male rats, cortical and hippocampal tissue of the injured hemisphere and matching contralateral material was harvested at early (4, 12 and 24 hours) and extended (3, and 7 days) timepoints post-procedure. Naïve rats that received only anesthesia were used as controls. Processed brain homogenates were assayed for chemokine and cytokine levels utilizing an electrochemilumenscence-based multiplex ELISA platform. The temporal profile of cortical tissue samples revealed a multi-phasic injury response following brain injury. CXCL1, IFNγ, IL4, and IL5 reached peak concentrations 4 hours post-injury and immediately returned to levels not different from control tissue. The levels of IL1b, IL13, and TNFa were also highest at 4 hours post-injury although their expression remained significantly above levels in uninjured tissue at extended time points. Additionally, IL1b and IL13 levels displayed a biphasic temporal profile in response to injury, which may suggest their involvement in an anti-inflammatory process. Interestingly, CCL2 and CCL20 did not reach peak levels until 1 day post-injury. Peak CCL2 levels were significantly higher than peak levels of any other inflammatory mediator measured, thus suggesting a possible use as a biomarker. Fully elucidating chemokine and cytokine signaling properties after brain injury may provide increased insight into a number of secondary cascade events that are initiated or regulated by inflammatory responses.